2018
DOI: 10.1159/000487101
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Baseline Osteoprotegerin Serum Levels and Prognosis of Advanced-Stage Colorectal Cancer Patients

Abstract: Background/Aims: Osteoprotegerin (OPG) is a soluble receptor of the pro-apoptotic cytokine TRAIL which is thought to contribute to tumour development by inhibiting apoptosis or affecting other aspects of tumour biology, including cell proliferation and immune response. Although immunohistochemical studies suggest that OPG correlates with survival in metastatic colorectal cancer (mCRC), only scarce data are available on serum OPG in CRC patients. Methods: In this pilot study, we assessed the prognostic signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, OPG can also act as an inhibitor of TRAIL, which induces tumor cell apoptosis (30) and high levels of OPG were associated with a higher cancer-related mortality in a large observational study with more than 6,000 patients (31). High levels of OPG have conferred a poor prognosis in patients with metastatic colorectal cancer (32). In prostate cancer, increased levels of OPG have been observed in patients with advanced cancer (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, OPG can also act as an inhibitor of TRAIL, which induces tumor cell apoptosis (30) and high levels of OPG were associated with a higher cancer-related mortality in a large observational study with more than 6,000 patients (31). High levels of OPG have conferred a poor prognosis in patients with metastatic colorectal cancer (32). In prostate cancer, increased levels of OPG have been observed in patients with advanced cancer (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of IL-8 because of polymorphisms in the IL-8/CXCR2 genes were associated with disease progression, disease recurrence, and drug resistance [ 43 , 44 , 45 , 46 ]. Furthermore, patients with COPD with frequent exacerbations were reported to have high levels of inflammatory markers, such as CRP [ 47 ], fibrinogen [ 47 ], IL-6 [ 48 ], soluble tumor necrosis factor-α receptors [ 37 , 49 , 50 ], and osteoprotegrin [ 37 ], which have been shown to be associated with the survival of patients with colorectal cancer [ 39 , 40 , 41 , 42 , 51 , 52 , 53 , 54 ]. In summary, the findings of our study are in line with those of previous studies regarding the COPD spillover hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…By this way, OPG can prevent tumor cell apoptosis and prolong cells’ survival time, which may partly explain the association between OPG and patients’ prognosis. In addition, it was reported that serum OPG levels were elevated in patients with advanced colorectal cancer (CRC) ( 19 ). Overexpression of OPG in CRC tissues was closely related with increased risk of tumor relapse and death, which was suggested as a potential prognostic biomarker for CRC patients.…”
Section: Discussionmentioning
confidence: 99%